The Master's Discourse: Dante und Petrarch in the Works of Stefan George - Walsh, John (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of German, 2026)
This thesis examines the works of Stefan George (1868-1933) from a predominantly intertextual angle, looking at the poet's use of intertextual references within the contexts of his oeuvre and his posing as master within the so-called George Circle. The two key points of reference, as read by this dissertation, are the Italian Trecento poets Dante Alighieri (1265-1321) and Francesco Petrarca (1304-1374). Dante and Petrarch represent, for George, two contrasting approaches to reality, one that is `infected' by a European tradition of literary love poetry (Petrarchism), another that is tempered by the legacy of German Romanticism. The dissertation builds upon existing George scholarship on his reception of both poets and presents its central argument that George's literary self-understanding must be viewed with both Dante's and Petrarch's contrasting poetics and reception histories in mind. In its reading of George's strategies of literary self-representation, it traces a poetic development that comes most fruitfully to light when considered under a specifically intertextual lens, for George stages what this study reads as a literary conversion from a Petrarchan poetics of alienated longing to a Dantean poetics of willpower and transcendence. It takes George's apparent rhetoric of transcendence seriously and probes it against a background of scholarship that is, on the whole, more insistent upon the poet's ideology of immanence, thereby raising the issue of transcendence in itself, and what it means in George's modernity. Despite his intimations of a Dantean prophetic vigour, the dissertation argues that the spirit of Petrarchan and Petrarchistic tradition continues to rear its head, even within the most Dantean of George's works. The issue of conversion arises here, and following established Petrarch and Dante scholarship, the thesis argues that Petrarchism and its lingering influence in George by design aims to inhibit successful conversion. The ground upon which this study moves is George's poetic language, and as such it is fundamentally philological in nature and concerned with words, tracing the development of George's Petrarchan and Dantean modi operandi across time. While the thesis is committed to its philological pursuits, the work of Slavoj Žižek provides one significant theoretical anchor for the close readings and analyses of George's writing worth mentioning here. Žižek's thought offers a uniquely applicable blend of Lacanian psychoanalytic insight alongside a critical theory of ideology as well as the philosophy of Friedrich Schelling. This theoretical mix is drawn upon, next to recent scholarship on George, in order to situate George within the specific context of German Dante reception, in which Schelling plays a central role. The thesis concludes with reference to recent scholarly work from both George studies and Dante studies in an attempt to bring both fields together and to consider the broader literary-theoretical implications of George's Dantism.
APPROVED
Keywords: Stefan George; Dante Alighieri; Francesco Petrarca; Petrarch; Petrarchism; modernism; intertextuality; George Circle